Peningkatan Kreativitas Perilaku Belajar Melalui Teknik Pemetaan Pikiran - Anggraeni, Tiara (Universitas Ahmad Dahlan, 2014)
The study was motivated by the lack of creativity in facilitating the learning behavior of receiving the material, making the situation uncomfortable in learning, improve behavior, learning, finding new ideas in the process of studying at SMK Negeri 5 Yogyakarta. This study aimed to test the classical guidance services using mapping techniques thought to enhance the creativity of student learning behavior. The method used in this research is classroom action research (Classroom action research), which will be conducted in two cycles of action. The research was conducted at SMK Negeri 5 Yogyakarta in XI class in Visual Communication Design A. The sampling technique in this study with purposive sampling, and subjects were 34 students. The instruments used are observation and questionnaires (questionnaires) in the form of Likert scale. The data were analyzed by using test product moment. The results showed that before the given actions that are in the lower categories, namely the frequency of the number 10 (29.45%), and the medium category with a number of frequency of 24 (70.6%). Once given the action in middle category by the number of frequency of 16 (47.1%), and are in the high category, with the number of frequency of 17 (50.0%), the category of very high that the number of frequency 1 (2.9%), Thus, there is an increase in creativity through the guidance of classical learning behavior in class XI student of Visual Communication Design A SMK Negeri 5 Yogyakarta. Information from this research can be useful for teachers BK BK services in developing techniques that one mind mapping technique in a variety of BK services to assist students in improving creativity learning behavior.